Phylogeny of Molossidae Gervais (Mammalia: Chiroptera) inferred by morphological data. (1st April 2015) - Gregorin, Renato; Cirranello, Andrea
Abstract: Molossidae is a large (roughly 100 species) pantropically distributed clade of swift aerially insectivorous bats for which the phylogeny remains relatively unknown and little studied compared with other speciose groups of bats. We investigated phylogenetic relationships among 62 species, representing all extant molossid genera and most of the subgenera, using 102 morphological characters from the skull, dentition, postcrania, external morphology, tongue, and penis, based on direct observation and literature reports. Both parsimony and Bayesian analyses were used in phylogenetic reconstruction. Our analysis supports two main clades of molossids, both of which mingle Old World and New World taxa. One clade is comprised of Mormopterus, Platymops, Sauromys, Neoplatymops, Molossops, Cynomops, Cheiromeles, Molossus, and Promops . The other clade includes Tadarida, Otomops, Nyctinomops, Eumops, Chaerephon, and Mops . The position of Myopterus with respect to these two groups is unclear. As in other recent analyses, we find that several genera do not appear to be monophyletic (e.g. Tadarida, Chaerephon, and Molossops sensu lato ). We recommend that the subgenera of Molossops sensu lato and Austronomus be recognized at the generic level. We conclude that much more data are needed to investigate lower level problems (generic monophyly and relationships within genera) and to resolve the higher‐level branching pattern of the family.